Tratamiento médico y otrasherramientas terapéuticas noquirúrgicas en endometriosissintomática - Céspedes, Pablo (2026)
Endometriosis is a disease that affects millions of women worldwide and significantly impacts their quality of life, including professional and psychological aspects.This article addresses the comprehensive management of symptomaticendometriosis, focusing on non-surgical therapeutic alternatives. The treatment of symptomatic endometriosis requires a personalized and multidisciplinary approach, combining medical therapies (both hormonal and non-hormonal), pelvic floor rehabilitation, and psychological support.Long-term medical therapy, including maintenance treatment after surgery, is often recommended to control pain and reduce recurrence. Throughout the process, the patient’s needs and active participation in treatment decisions should be prioritized.